2004
DOI: 10.1007/s00204-003-0528-x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of pituitary hormone-immunoreactive cell populations in rat offspring after maternal dietary exposure to endocrine-active chemicals

Abstract: We previously performed dose-response studies of genistein, diisononyl phthalate, 4-nonylphenol, methoxychlor (MXC), and bisphenol A to examine the impact of maternal dietary exposure from gestational day 15 to postnatal day 10 on the development of rat reproductive system in later life. Among the chemicals MXC alone showed typical estrogenic effects only at the maternally toxic 1200 ppm. The present study was performed to examine the sensitivity of immunohistochemical analysis of pituitary cells of offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The Crl:CD (SD) rat strain is insensitive to BPA, and 0 of 13 studies report low dose effects [155][156][157][158][159][160][161][162][163][164][165][166][167]. In addition, this rat strain is insensitive to the drug ethinylestradiol at doses (~0.5 μg/kg/day) used in oral contraceptives [163,167]. As shown above, a large number of studies show that significant low-dose effects of BPA have been observed in the original Sprague-Dawley rat.…”
Section: Strain Differencesmentioning
confidence: 99%
“…The Crl:CD (SD) rat strain is insensitive to BPA, and 0 of 13 studies report low dose effects [155][156][157][158][159][160][161][162][163][164][165][166][167]. In addition, this rat strain is insensitive to the drug ethinylestradiol at doses (~0.5 μg/kg/day) used in oral contraceptives [163,167]. As shown above, a large number of studies show that significant low-dose effects of BPA have been observed in the original Sprague-Dawley rat.…”
Section: Strain Differencesmentioning
confidence: 99%
“…Experiment 2 is inadequate for consideration due to inappropriate statistics that failed to account for litter effects. Masutomi et al (2004), supported by the Japanese Ministry of Health, Labour, and Welfare, examined the potential effects in rats of neonatal bisphenol A exposure through maternal dietary intake on the number of offspring pituitary cells positive for LH, FSH, and prolactin. The authors exposed 5-8 pregnant CD(SG)IGS dams from GD 15-PND 10 to soy-free diet containing: (1) genistein 20, 200, or 1000 ppm; (2) diisononyl phthalate 400, 4000, or 20,000 ppm; (3) methoxyclor 24, 240, or 1200 ppm; (4) 4-nonylphenol 60, 600, or 3000 ppm; or (5) bisphenol A [96.5% purity] 60, 600, or 3000 ppm.…”
Section: Experimental Animalmentioning
confidence: 99%
“…Although some studies show that treatment with MXC alters GnRH mRNA levels in the POA in adult female rats [208], oral exposure to 1200 ppm MXC during fetal and neonatal periods, did not affect the size of the SDN-POA in the hypothalamus [209]. In contrast, similar oral developmental exposure caused an increase in PR in the POA of adult female rats [210] and altered the number of gonadotropes and lactotropes in the pituitary [211]. More recently, it was shown that MXC exposure during fetal and neonatal periods altered ERα gene expression in the POA in aged (17–18 months) female rats [212].…”
Section: Edcs and Their Effects On The Female Reproductive Systemmentioning
confidence: 99%